2017
DOI: 10.1515/rjr-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sinoliths in the ethmoid sinus – a rare Cone Beam CT finding

Abstract: Sinoliths are calculi found particularly in paranasal sinuses, the rarest location being the ethmoid air cells. There were previously reported only 4 cases of unilateral large ethmoidal sinoliths (ES), this one being the fifth report. We report here the incidental bilateral evidence in a 34-year-old female patient evaluated in Cone Beam Computed Tomography (CBCT) of minor ES. The left ES, of 1.6 mm2 sagittal size, occupied the suprabullar cell, in front of the ground lamella and behind the anterior ethmoidal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This study demonstrated that CBCT could be a more reliable tool for the evaluation of nasal pneumatizations, as previously assessed. 12,29,31 The need for CBCT prior to any surgical procedure should be determined on a case-by-case basis, as the common Vesalian anatomy is frequently overridden by anatomical variations. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that CBCT could be a more reliable tool for the evaluation of nasal pneumatizations, as previously assessed. 12,29,31 The need for CBCT prior to any surgical procedure should be determined on a case-by-case basis, as the common Vesalian anatomy is frequently overridden by anatomical variations. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…These criteria are important factors in the radiographic interpretation of soft tissue radiopacities. 3,16 So that, dentists should identify, diagnose, treat or refer for treatment all pathological findings on radiographs. A combination of clinical, dental and radiographic examinations help to confirm most soft tissue calcifications and if needed additional radiographic method may be used to detect them.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sinolith in the ethmoidal sinus is very rare and only 5 cases in the English literature were documented with ethmoidal sinolith as mentioned by Sava and Rusu. 16 Our case is considered the 6th one. There were 3 cases with uncertain final diagnosis as their radiographic features didn't resemble the radiographic criteria to any of the soft tissue calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…Sinoliths are rarely encountered calculi lodged in the paranasal sinuses 1 . They are also termed antroliths, rhinoliths, antral calculi, antral stones, or antral rhinoliths 2 .…”
Section: Introductionmentioning
confidence: 99%
“…They are also termed antroliths, rhinoliths, antral calculi, antral stones, or antral rhinoliths 2 . There were reported sinoliths of the maxillary sinus 3 , ethmoidal sinuses 1,[4][5][6] , frontal sinuses 7,8 . The most rarely reported are the sphenoidal sinoliths.…”
Section: Introductionmentioning
confidence: 99%